Advanced short fiber composites with hybrid reinforcement and selective fiber-matrix-adhesion based on polypropylene – Characterization of mechanical properties and fiber orientation using high-resolution X-ray tomography. (August 2018) - Kahl, C.; Feldmann, M.; Sälzer, P.; Heim, H.-P.
Abstract: Composites with two types of reinforcement fibers open a large field of opportunities and combine properties. Glass fibers lead to higher strength and modulus, but they provide a brittle character. In contrast to this, man-made cellulose fiber composites show higher energy absorption and higher elongation-at-break. The aim of this study is to investigate the synergy of those two fiber types in a hybrid compound. Compounds with an overall fiber content of 16 vol% and different ratios of glass and man-made cellulose fibers were prepared with a twin-screw extruder and injection molded to test specimen. Mechanical properties as well as the composite morphology were studied for compounds with selective fiber-matrix-adhesion and without a coupling agent. A bimodal fiber length distribution was found in the hybrid compounds due to the different shortened fiber types. The long man-made cellulose fibers increase the impact strength and influences the fiber orientation in the hybrid.